Web-based RIG performance reporting system using interactive visualization techniques / Amir Hambaly Nasaruddin - Nasaruddin, Amir Hambaly (2019)
The development of Web-Based RIG Performance Reporting System is a solution to the CoRe department to generating the report from the system. This system can visualize the data from the database in order to analyze the performance. The problem occurs when CoRe department needs to generate a report of RIG performance, they are using manual approaches. With this system, CoRe department does not need to use a manual approach to analyze the content. A study found that the visualization tools nowadays are not free, and it is expensive, so this system will help CoRe department in visualizing data. This project software development process used an agile model SDLC to develop the system. The system architecture which consists of a user interface, web framework and storage data. D3.js is used as a technology to visualize the result in interactive form or dynamic visualization which is a JavaScript library and Python is a language to program the system. For the user to analyze the result, the system provides visual analytics technique which can educate the user on analyzing the result which is drill down and sorting function to educate users. The result of this project is all algorithm for visualizing data is functioning and the output produced from the system is correct and effective. A conclusion that can be made is the development of WebBased RIG Performance Reporting System is important for helping CoRe department in generating the report and help them to understand the significance of data in visual context.